PERAN HUKUM ADMINISTRASI DALAM PENGATURAN KEMITRAAN PUBLIK-SWASTA DALAM PEMBANGUNAN INFRASTRUKTUR - Sami'an, Sami'an; Mustakim, Mustakim; Marhayudi, Putut; Taufiq, Taufiq; Taufiqurrohman , A.H. Asari (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2024)
Optimizing the growth of infrastructure development in the construction services sector requires synergy between the city government and the private sector (contractors) in the implementation of development, and financing cooperation certainly requires cooperation with investors. Tracing the development of the dynamics of the implementation of regional autonomy in the era of advanced development in Indonesia shows that local governments have a huge potential to cooperate with third parties in accordance with Article 195 of the Regional Government Law Number 23 of 2014. The method used in this article is a literature review, as it allows a thorough study of the theoretical and practical aspects of cooperation agreements in the infrastructure sector. The main focus is on legal factors such as liability, risk sharing and the rights and obligations of both parties. Analyze the role of law in public-private relations in the context of infrastructure projects. In each agreement made, the state has a special position in the contractual relationship with its partners, as well as in the formalization, implementation, and enforcement stages